PELATIHAN ECOMMERCE PADA INDUSTRI RUMAH TANGGA DI DESA DANGDANG UNTUK MENINGKATKAN PENDAPATAN SEBAGAI DAYA SAING MASYARAKAT DI ERA DIGITAL - Agus Heri Yunial; Joko Suwarno; Wilis Puspita Sari (Abdi Jurnal Publikasi, 2023)
Today's technology continues to grow and the benefits of using the internet are felt for the users. Some people feel dependent on the internet, including the activities of Micro, Small and Medium Enterprises (MSMEs) in utilizing information technology to run their business, especially in the digitalization era. Indonesia is known as a region that has a variety of regional superior products and is the hallmark of a village, sub-district, district or province. Regional superior products have the potential to be further developed according to natural conditions and the local environment, so that they can be competitive and can improve people's welfare. The superior product development program will also be more successful if it is supported by the participation of the regional government, especially in terms of coordination and provision of policies that are in favor of MSMEs producing regional superior products. Application of Science and Technology (Science and Technology) from universities as an effort to develop regional superior products, competitive in the domestic market and even reaching dynamic overseas. Therefore, through community service activities, university lecturers, in this case the lecturers at Pamulang University in the Informatics Engineering study program, took a role in socializing the role of information and communication technology in e-commerce training activities for home industries in Dangdang village to increase income as a competitive advantage. society in the digital era to help the MSME community in Dangdang Village in developing their business in order to increase their income from the sale of their products. The e-commerce used is the Shopee application.